Analysis of Students’ Mathematical Representation Ability in Working on Conical Section Problems - Yuwono, Muhammad Ridlo; Firmansah, Fery; Syaifuddin, M. Wahid (Edumatica : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze students’ representational ability in working on conic section problems. This study is included in case study research using a qualitative approach. The subjects of this study were students of Widya Dharma University. This study used the primary instrument (researcher) and auxiliary instruments (tests and interview guidelines). The validity of this research data was supported by triangulation techniques that compared the results of the conic section test work with those of the interview. The data analysis stage of this study consisted of data condensation, data presentation, and conclusion. The results of this study are presented as a profile of students’ representational ability when working on geometry problems. In ellipse, parabola, and hyperbola problems, writing important information in the problem, not making analogies, and writing incorrect equations. The profile of students’ visual representation ability shows that they are unable to draw sketches of ellipse, parabola, and hyperbola graphs correctly. In ellipse, parabola, and hyperbola questions, the problem is that they do not provide explanatory sentences for each stage of working on the questions.